ALTERNATIVE ASSESSMENT DURING THE PANDEMIC: TEACHERS OF ENGLISH PERSPECTIVE - Свиридова, Лариса; Ямшинская, Наталья; Чугай, Оксана; Куценок, Неонила (SWorldJournal, 2021)
Alternative assessment as a formative type of assessing students’ progress and achievements is a tool to achieve the 21st-century learning goals. The authors’ purpose is to provide the readers with the analysis of alternative assessment approaches and get